P502 Dietary habits and nutritional status in children and adolescents with Inflammatory Bowel Disease: an italian multicenter case-control study (NUTRIBD study). (27th May 2021) - Gatti, S; Vallorani, M; Zoppi, E; Aloi, M; Bramuzzo, M; Felici, E; Panceri, R; Ciacchini, B; Catassi, G; Grazian, F; Catassi, C
Abstract: Background: Nutrition is involved in several aspects of pediatric IBD, ranging from disease etiology to induction and maintenance of disease. Presence of nutritional deficiencies can influence clinical outcomes and affect the immune system, growth and sexual maturation in children. Few studies assessed the dietary intake of IBD's pediatric patients and investigated whether their dietary intakes meet the recommended daily allowances (RDA). Methods: Children and adolescents with a diagnosis of IBD (> 1 year) and healthy controls (age and gender matched) were prospectively enrolled in 5 pediatric Italian IBD units. Daily dietary intake in the previous 6 months was assessed using a Food Frequency Questionnaire (FFQ). Energy intake (EI) and macro and micronutrients intakes were compared to the national RDA (LARN) and EI to the predicted total energy expenditure (TEE) based on the Schofield equation. Adherence to the Mediterranean diet was measured through the KIDMED score. Clinical and auxological data were recorded Results: 110 IBD subjects and 110 controls (median age±SD: 14, 6 ±2, 2 and 13, 8±2, 8 years, p= 0, 45) were enrolled. Weight and height z-scores were significantly lower in IBD compared to controls (p= 0, 0005 and p=0, 036).Weight, height and BMI z-score did not differ between CD and UC. EI (Kcal/day), the EI/RDA ratio (%) and the EI/TEE ratio (%) were significantly lower in IBD compared to the controls (1893 vs 2068 kcal/day, p= 0, 009; 71, 5% vs 84, 7%, p< 0, 0001; 79, 8% vs 90, 8%, p=0, 007). When distributing patients by clinical disease activity, the TEE was lower in patients with active disease compared to patients in remission (1850 vs 1915; p=0, 039). A significant correlation was not found between age, gender, type of disease, disease activity, and EI/RDA % and EI/TEE %. Total protein and fat intake were lower in children with IBD compared to controls. Conversely the total carbohydrate intake did not differ between IBD patients and controls (median 289, 8 vs 311, 7 gr/day, p= 0, 077) while the percentage of carbohydrate to EI was higher (CHO % : 61 vs 58; p=0, 012). Total charbohydrates intake was significantly lower in patients with active disease compared to patients in remission (265.7 vs 294.3 gr/day; p=0, 002). IBD patients reported a lower intake of the main dietary micronutrients compared to controls. A poor adherence to the Mediterranean diet was more frequent in IBD children (37.2% vs 22.7%, p= 0, 013). Conclusion: The diet of Italian children and adolescents with IBD differs substantially from the general pediatric population and frequently does not meet the RDA. Our data suggest the need of an accurate evaluation of the dietary intake and nutritional status in order to prevent nutritional deficiencies and promote health.